The Role of Digital Technology and Regulations in the Diffusion of Mobile Phones in Asia (The Pakistan Development Review, 2000)
More and more people are using mobile (cellular) phones and the world is increasingly becoming unwired due to diffusion of this technology. The cellular technology is present in most Asian countries since 1980s. However, its diffusion process in these countries has largely been affected by technological developments, i.e., transition from analogue to digital, and regulations. The nature of regulations relate to spectrum licensing and the number of competitors allowed by respective governments. These regulatory decisions may explain the current structure of mobile phone industry in most of these countries. The popularity of cellular communication lies in its appealing advantage as compared with the fixed networks. The most important feature of a cellular phone is its portability in that the call is made to a person and not to a place. In developed countries, the features available on mobile handsets (such as caller line identification, voice mail, call forwarding, call waiting and the facility of receiving and transmitting short text messages) are available free of charge. However, these cell phone facilities are very costly in developing countries as compared with their fixed networks. The regulatory licensing structure prevailing in these countries partly explains this price differential. In effect there has been wide diversity in the speed of introduction of mobile phones and their diffusion across developing countries, which has not been explored. Gruber and Verboven (1998) has recently examined diffusion of cell phones in the European Union. However, this is a neglected area of research in developing countries.